Analisa Perbandingan Model Birokrasi Indonesia: Model Modern David Osborne, Ted Gaebler dan Pendekatan Konsep Islam Perspektif Umer Chapra - Yulizar D Sanrego; Reza Muhammad (AL-MUZARA'AH, 2013)
The inefficiency of public service in Indonesia is one of the results of badbureaucracy, so that the development system becomes stagnant. On the contrary, sustainabledevelopment is a reflection of a good bureaucracy. So far Indonesia is still ranked 100th out of182 countries in the world for corruption. This paper aims to find out the bureaucratic model inIndonesia within the framework of modern bureaucratic model as well as Islamic Conceptapproach of Chapra’s perspectives. Using content analysis, the paper found that Indonesianbureaucracy model still embrace patrimonial concept that vulnerable to the practice ofcollusion, corruption and nepotism. While the modern model of Osborne and GaeblerEntrepreneurial Bureaucracy concept with the spirit of innovation and creativity has brought agood change and it is in line with Islamic model of Chapra’sperspective. Chapradescribes thatthe development of a country should be run simultaneously with the bureaucracy that promotesIslamic values, moral, and hard work. It is concluded that by applying this concept,bureaucracy in Indonesia will be more effective in removing socio-economic problem and willcome up with more efficient and sustainable development dimensions.